Kriopreservasi Sperma Manusia: Systematic Review - Diana Fadhilah; Adam Raihan Priambada; Zozy Aneloi Noli; Rita Maliza (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify the types of methods and effects of human sperm cryopreservation. This review was written using a literature review method from international databases such as Scopus and PubMed. The results of the research show that by choosing a cryopreservation method, choosing a cryoprotectant agent such as TAT-PRDX2, canthaxanthin, or Holotheria parva coleomic extract, can increase sperm motility, viability and integrity after cryopreservation, the right cryoprotectant agent can defend cells from oxidative stress and fragmentation DNA. Keywords: Cryopreservation, Human, Sperm